SALES PERFORMANCE IMPROVEMENT MODEL BASED ON INTRINSIC RELIGION, HALAL PRODUCT KNOWLEDGE, AND SERVICE VALUE CAPABILITY - Irfan Rahmana; Ken Sudarti; Muhammad Athharuddin Sofyan (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study aims to identify the effect of intrinsic religiosity, halal product knowledge, and service value capability on the sales performance value of sharia insurance products. The population of this study was all sharia insurance agents from Prudential insurance in Semarang city. The population in this study was unknown exactly, so the number of samples was calculated using Slovin formula and 150 people were obtained as the sample through the snowball sampling method. Multiple linear regression used analytical tool in analysing the value of the research quantitative data. This study has succeeded in proving that sales performance of sharia insurance salesmen can be realized through service value capability, intrinsic religiosity and Halal Product Knowledge. The results of this study are very useful for strengthening the halal ecosystem by strengthening "people" who are very important in-service companies including sharia insurance services. Furthermore, the capability of salesmen in delivering service value will be a solid basis of differentiation for strengthening the competitive advantage of sharia insurance.